POLA ASUH ORANGTUA, KONSEP DIRI REMAJA DAN PERILAKU SEKSUAL - Delfriana Ayu Astuti, SST., M.Kes (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2016)
ABSTRACTUnhealthy sexual behavior among the teenagers, especially in those who are still single, tends to be increasing. The factor that can influence the forming of the teenagers’ self-concept on the sexual behavior are parenting patter.The purpose of this quantitative study with cross-sexual approach was to find out the influence of parenting pattern on the self-concept of the teenagers on sexual behavior at SMA Dharma Bakti Medan. The population of this study was all of the 90 students of Class X and XI and all of them were selected to be the samples for this stufy. The data for this study were obtained through questionnaire distribution. The most parenting pattern the teenager had was that of their democratic father and mother (61.1%). The combination of parenting patterns (democratic father and authoritarian mother) had a significant relationship with the self-concept of teenagers on sexual behavior with level of significance = 0.003 and had positive influence on the concept of teenagers. The management of the school is suggested to instill more discipline to generate attitude and disciplined behavior in the students that they can be prevented from any behavior which is not in accordance with the norms practiced in the society. Keywords :Parenting Pattern, Self-Concept, Sexual Behavior, Teenagers, Students